2009
DOI: 10.1088/0034-4885/72/7/076501
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond superradiant emission in inorganic semiconductors

Abstract: A review of an experimental study of superradiance in semiconductor inorganic structures is presented. It is demonstrated that unique properties of superradiant emission are determined by unusual properties of electrons and holes, namely, the formation of BCS-like state in a system of collectively paired electrons and holes. This can adequately explain all features of superradiance, including its femtosecond pulse duration, record peak power, optical spectrum, spatial and temporal coherency and macroscopically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 77 publications
(176 reference statements)
7
45
0
Order By: Relevance
“…Likewise, the interaction between the SR sample and the external radiation field can be visualized in the uncoupled basis with the same diagram as in figure 6 (with the appropriate basis, i.e., replacing in the figure b c , 1; , 0ñ | with c 1; , 0ñ | , etc.). Accordingly, the eigenvalues of these new dressed states are reminiscent (though not the same) as those found in equations (13)- (16) and suggest that we can make the following approximate substitution…”
supporting
confidence: 54%
“…Likewise, the interaction between the SR sample and the external radiation field can be visualized in the uncoupled basis with the same diagram as in figure 6 (with the appropriate basis, i.e., replacing in the figure b c , 1; , 0ñ | with c 1; , 0ñ | , etc.). Accordingly, the eigenvalues of these new dressed states are reminiscent (though not the same) as those found in equations (13)- (16) and suggest that we can make the following approximate substitution…”
supporting
confidence: 54%
“…It consists in incorporating a saturable absorber [17] (see also Introduction and Section II.C). Technically this is AlGaInAs and GaN QW lasers [36][37][38][39]. Unfortunately all experimental studies reported in the literature do not distinguish the first emission burst from the subsequent self-pulsations, which can be modulated with a Q-switching pulse envelope.…”
Section: E the Role Of Carrier Diffusionmentioning
confidence: 99%
“…If the initial number of excited emitters n in the Dicke state is smaller than N, then the transition time to the , / 2 N N state decreases because of the decrease in the number of terms in the sum in Eq. (7). As the number of excited emitters approaches N/2, the delay time tends to zero.…”
Section: The Dicke Model Of Supperradiancementioning
confidence: 98%